Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In Shreve's book on pp. 37-39 I read that given a standard normal random variable $X \sim N(0, 1)$ and another random variable $Y = X+ \theta$, we can define a measure change

$$\frac{d \widetilde{\mathbb{P}}}{d \mathbb{P}} = Z = \exp\left(-\theta X - \tfrac12\theta^2\right)$$

so that under $\widetilde{\mathbb{P}}$ the random variable $Y$ has the same distribution as $X$ under the original probability measure.

I am trying to extend it to the case when $X \sim N(\mu, \sigma^2)$. I guessed that in this case: $$Z = \exp\left(\frac{-\theta (X - \mu) - \tfrac12\theta^2}{\sigma^2}\right)$$

and the integration seem to confirm (if I haven't made a mistake that is) that it indeed works as expected.

However, when I used it in a simulation then for small $\sigma$ the average of the simulated $Z_i$ was much lower than 1 (whereas for the measure change we should have $\mathbb{E}[Z] = 1$). For $\sigma=1$ the simulation works perfectly, which makes me think that I made a mistake somewhere.

What I am doing wrong? What is the correct measure change?

share|cite|improve this question
how did you create the simulation? i am working on something similar. specifically, once you change measures how do you simulate from it? do you simply use the standard density inversion, generate uniform rv, etc.? – Alex Oct 10 '15 at 2:59

Yours is the correct change of measure.

The random variable $U=(X-\mu)/\sigma$ is standard normal hence its Laplace transform is such that $\mathrm E(\mathrm e^{-\lambda U})=\mathrm e^{\lambda^2/2}$ for every $\lambda$. Furthermore, $Z=\mathrm e^{-\theta^2/(2\sigma^2)}\mathrm e^{-\theta U/\sigma}$ hence $$\mathrm E(Z)=\mathrm e^{-\theta^2/(2\sigma^2)}\mathrm E(\mathrm e^{-\lambda U}),$$ for $\lambda=\theta/\sigma$, that is, $\mathrm E(Z)=\mathrm e^{-\theta^2/(2\sigma^2)}\mathrm e^{\lambda^2/2}=1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.